Dinamika Dan Faktor Yang Memengaruhi Permintaan Tenaga Kerja Sektor Konstruksi Di Indonesia - Chairil Mihran; Ramdan Althaf (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2023)
The pandemic that occurred in 2020 had quite an impact on the world economy, one of which was in Indonesia. In Indonesia itself, many people who have experienced an economic downturn from the trade, business and tourism sectors are feeling the impact. The impact of the economic downturn was also felt by people in rural areas. In the midst of declining economic conditions in society, social entrepreneurship is needed as a solution to revive economic conditions and overcome social problems in Indonesia, especially in rural areas. Economic improvement in rural areas can be done with the presence of social entrepreneurship. Villages with attractive potential can be a source of increasing the community's economy by holding a tourism village-based business. The community's role and government's attention are needed to support the improvement of the tourism village-based community economy. Therefore, synergy between the community and the local government is needed to overcome this problem. One of these solutions is to see the potential that exists in the village and develop it into a tourist village. Cangkringan itself has seven criteria according to Hadiwijoyo's statement (2012). The role of the local government is needed for the realization of Cangkringan to become a tourist village.